Samarium-cobalt magnet with high mechanical property and preparation method of samarium-cobalt magnet
Through alternating powder laying and pressing and sintering solid solution treatment, a heterogeneous structure was constructed, which solved the problem of poor mechanical properties of 2:17 samarium cobalt magnets, and achieved a combination of high bending strength and excellent magnetic properties.
Patent Information
- Application Number
- CN202411579356.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-07
AI Technical Summary
Due to its complex main phase crystal structure, few slip systems and strong anisotropy of magnetite, it is prone to defects such as corners and edge drops, which limits its application in high-end equipment and is currently available. Methods to improve mechanical properties have a great impact on magnetic properties.
Through the alternating powder laying and pressing method, samarium-cobalt A powder and samarium-cobalt B powder are arranged alternately according to different weight and particle size to build a heterogeneous structure, and combined with sintering solid solution and aging treatment to form a coarse crystal region and fine crystal region. Improve mechanical properties while ensuring magnetic properties.
The bending strength and magnetic energy production of samarium-cobalt magnets are significantly improved, ensuring that the magnetic properties are not damaged, and at the same time improving the overall mechanical properties of the material.
Smart Images

Figure CN119274907A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of magnetic materials, and in particular to a samarium cobalt magnet with high mechanical properties and a preparation method thereof. Background Art
[0002] 2:17 SmCo magnets have high Curie temperature, good temperature stability and strong corrosion resistance, and are widely used in high-end magnetic power fields such as high-speed and high-temperature motors. However, due to the complex main phase crystal structure, few slip systems, strong magnetocrystalline anisotropy and other characteristics of 2:17 SmCo magnets, they are prone to fracture and breakage. They are prone to defects such as missing corners and falling edges during inspection, transportation, and magnetization. This not only limits their assembly accuracy in motors, but also makes them easy to break during work, seriously affecting the stability of the overall components and severely restricting the further application of SmCo magnets in high-end equipment and other fields. Therefore, improving the mechanical properties of 2:17 SmCo magnets has become an urgent problem to be solved.
[0003] At present, there are two main methods to improve the mechanical properties of magnets. The first is to add high-melting-point metals or alloys. The addition of high-melting-point metals or alloys will have the effect of dispersion strengthening and toughening, thereby improving mechanical properties such as toughness and strength, but will reduce the magnetic properties. The second is surface treatment. Surface coating can improve the mechanical properties to a certain extent, but the effect is not significant and will affect the magnetic properties.
[0004] Therefore, it is necessary to develop a method for preparing a 2:17 type samarium cobalt magnet that can improve the mechanical properties of the magnet and has less influence on the magnetic properties. Summary of the invention
[0005] In view of the above analysis, the present invention aims to provide a high mechanical property samarium cobalt magnet and a preparation method thereof, so as to ensure the magnetic properties of the samarium cobalt magnet and improve the mechanical properties of the samarium cobalt magnet.
[0006] On the one hand, the present invention provides a preparation method of a samarium cobalt magnet with high mechanical properties, comprising a powder spreading and pressing step, wherein samarium cobalt A powder and samarium cobalt B powder are alternately spread to ensure that the bottom layer and the top layer are samarium cobalt B powder, and the particle sizes of the samarium cobalt A powder and the samarium cobalt B powder are different; the weight of the samarium cobalt A powder is 5wt.%-50wt.%, and the weight of the samarium cobalt B powder is 95wt.%-50wt.%.
[0007] Furthermore, the samarium cobalt A powder is divided into n parts by weight, and the samarium cobalt B powder is divided into n+1 parts by weight, wherein n≥3.
[0008] Furthermore, the weight of the samarium cobalt A powder is 5wt.%-35wt.%, and the weight of the samarium cobalt B powder is 95wt.%-65wt.%.
[0009] Furthermore, the particle size of the samarium cobalt B powder is larger than that of the samarium cobalt A powder. The particle size of the samarium cobalt A powder is 1-2 μm, and the particle size of the samarium cobalt B powder is 3-4 μm.
[0010] Furthermore, the mixed powder is placed in a magnetic field with a magnetic field strength of 1.8T-2.0T for orientation molding, and then cold isostatic pressing is performed at a pressure of 180MPa-300MPa for 10-60 seconds to obtain a samarium cobalt blank.
[0011] Furthermore, a smelting and powdering step is also included before the powder spreading and pressing step. The compositions of the samarium cobalt A powder and the samarium cobalt B powder are: Sm content 24-26wt.%, Fe content 17-20wt.%, Cu content 4-7wt.%, Zr content 2-3wt.%, and the rest is Co.
[0012] Furthermore, after the powder pressing step, a sintering and solid solution step is also included. The sintering conditions are heating to 200°C-500°C, keeping the temperature for 0.5-2h, then heating to 1195-1220°C, and keeping the temperature for 0.5-5h.
[0013] Furthermore, an aging treatment step is also included after the sintering and solid solution step to obtain a samarium cobalt magnet; wherein the aging temperature is 800-900°C, the holding time is 4-24h, the temperature is reduced to 350-500°C at a cooling rate of 0.5-2°C / min, and the temperature is kept for 2-15h.
[0014] Furthermore, the magnetic energy product of the samarium cobalt magnet is above 28 MGOe, and the bending strength is above 140 MPa.
[0015] On the other hand, the present invention provides a samarium cobalt magnet with high mechanical properties, which is prepared by the preparation method of the present invention.
[0016] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0017] 1. In the present invention, samarium cobalt A powder and samarium cobalt B powder with different particle sizes are arranged alternately to ensure that the bottom and top layers are samarium cobalt B powder. The alternating powder spreading method can construct a heterogeneous structure, which has a special structure composed of regions with significantly different mechanical or physical properties. By constructing coarse-grained and fine-grained regions in samarium cobalt, different soft and hard regions are formed. During the deformation of the material, back stress is formed in the soft region and front stress is formed in the hard region. Together, they lead to the heterogeneous deformation induced (HDI) strengthening effect, thereby significantly improving the mechanical properties. And this heterogeneous structure has no effect on the composition of the magnet, so it can have less impact on the magnetic properties;
[0018] 2. In the present invention, the particle size of the SmCoB powder is larger than that of the SmCoA powder. For example, the particle size of the SmCoA powder is 1-2 μm, and the particle size of the SmCoB powder is 3-4 μm; the weight of the SmCoA powder is 5wt.%-50wt.%, and the weight of the SmCoB powder is 95wt.%-50wt.%; the particle size and weight of the SmCoA powder and the SmCoB powder need to be strictly controlled within the above range, and the obtained magnet has not only high bending strength, but also excellent magnetic properties. After testing, the bending strength of the obtained SmCo magnet is above 145MPa, and the maximum magnetic energy product is above 28.11MGOe.
[0019] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0021] Figure 1 is a scanning electron microscope image of Example 1;
[0022] Figure 2 is a scanning electron microscope image of Example 2;
[0023] Figure 3 is a scanning electron microscope image of Example 3;
[0024] Figure 4 is a scanning electron microscope image of Example 4;
[0025] Figure 5 This is the scanning electron microscope image of Comparative Example 2. DETAILED DESCRIPTION
[0026] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0027] At present, 2:17 samarium cobalt magnets are widely used in high-end magnetic power fields such as high-speed and high-temperature motors due to their high Curie temperature, good temperature stability and strong corrosion resistance. However, due to their poor mechanical properties, especially bending strength, they are prone to defects such as missing corners and falling edges during inspection, transportation and magnetization, which affects their use.
[0028] There are two main methods to improve the mechanical properties of samarium cobalt magnets: one is to add high melting point metals or alloys; the other is to coat the samarium cobalt magnets. Although it can improve the mechanical properties of samarium cobalt magnets, it will also affect the magnetic properties of samarium cobalt magnets.
[0029] Therefore, the present invention provides a preparation method of a samarium cobalt magnet with high mechanical properties, comprising a powder spreading and pressing step, wherein samarium cobalt A powder and samarium cobalt B powder are alternately spread to ensure that the bottom layer and the top layer are samarium cobalt B powder, and the particle sizes of the samarium cobalt A powder and the samarium cobalt B powder are different; the weight of the samarium cobalt A powder is 5wt.%-50wt.%, and the weight of the samarium cobalt B powder is 95wt.%-50wt.%.
[0030] Compared with the prior art, the present invention provides a preparation method of samarium cobalt magnets, which changes the powder spreading method, replacing the traditional mixed powder spreading with alternating powder spreading, that is, two kinds of samarium cobalt A powder and samarium cobalt B powder with different particle sizes are regularly alternately spread, that is, B powder-A powder-B powder...B powder-A powder-B powder, ensuring that the bottom layer and the top layer are B powder, and controlling the weight of the samarium cobalt A powder and the samarium cobalt B powder.
[0031] The use of alternating powder laying can construct a heterogeneous structure, which has a special structure composed of regions with significantly different mechanical or physical properties. By constructing coarse-grained and fine-grained regions in samarium cobalt, different soft and hard regions are formed. During the deformation of the material, back stress is formed in the soft region and front stress is formed in the hard region. Together, they lead to the heterogeneous deformation induced (HDI) strengthening effect, thereby significantly improving the mechanical properties. And this heterogeneous structure has no effect on the composition of the magnet, so it can have less impact on the magnetic properties.
[0032] After subsequent preparation, sintering, solid solution treatment and aging treatment, not only the bending strength of the samarium cobalt magnet can be improved, but also the magnetic properties of the samarium cobalt magnet can be guaranteed. The magnetic energy product of the samarium cobalt magnet is above 28MGOe and the bending strength is above 140MPa.
[0033] In the present invention, the weight of the samarium cobalt A powder can be 5wt.%, 15wt.%, 20wt.%, 25wt.%, 30wt.%, 35wt.%, 40wt.%, 45wt.% or 50wt.%.
[0034] In the present invention, the weight of the samarium cobalt B powder can be 95wt.%, 90wt.%, 85wt.%, 80wt.%, 75wt.%, 70wt.%, 65wt.%, 60wt.%, 55wt.% or 50wt.%.
[0035] Preferably, the weight of the samarium cobalt A powder is 5wt.%-35wt.%, and the weight of the samarium cobalt B powder is 95wt.%-65wt.%.
[0036] It should be noted that in the present invention, the weight of the samarium cobalt A powder and the samarium cobalt B powder needs to be strictly controlled. The weight of the samarium cobalt A powder shall not be greater than the weight of the samarium cobalt B powder. When the weight of the samarium cobalt A powder is too much, it will lead to incomplete cellular structure of the magnet, and ultimately reduce the magnetic properties of the magnet.
[0037] Specifically, the samarium cobalt A powder is divided into n parts by weight, and the samarium cobalt B powder is divided into n+1 parts by weight, wherein n≥3.
[0038] Preferably, 3≤n≤8.
[0039] It should be noted that in the present invention, the alternating powder spreading method is required to construct a heterogeneous structure, and the samarium cobalt A powder and the samarium cobalt B powder need to be equally divided, and the number of samarium cobalt B powder is 1 more than the number of samarium cobalt A powder. In the process of equal division, if the number of portions is too small, the effect of constructing a heterogeneous structure is not obvious, and the effect of improving mechanical properties is not obvious or has no effect, so the number of portions needs to be controlled to be more than 3 powders, that is, n ≥ 3. In order to take into account the actual operation, it is necessary to control n to be less than 8 portions.
[0040] Specifically, the particle size of the samarium cobalt A powder is 1-2 μm, and the particle size of the samarium cobalt B powder is 3-4 μm.
[0041] It should be noted that in the present invention, the particle sizes of samarium cobalt A powder and samarium cobalt B powder need to be strictly controlled, and the particle sizes need to be different. Small particle sizes constitute fine-grained areas, while large grains constitute coarse-grained areas, and form different soft and hard areas. During the deformation of the material, back stress is formed in the soft area and front stress is formed in the hard area, which together lead to the heterogeneous deformation induced (HDI) strengthening effect, thereby significantly improving the mechanical properties.
[0042] Specifically, the mixed powder is placed in a magnetic field with a magnetic field strength of 1.8T-2.0T for orientation molding, and then cold isostatic pressing is performed at a pressure of 180MPa-300MPa for 10-60 seconds to obtain a samarium cobalt blank.
[0043] It should be noted that, in the present invention, the samarium cobalt A powder and the samarium cobalt B powder are mixed in an alternating powder spreading manner, and then the powders are oriented and molded in a magnetic field and cold isostatically pressed to obtain a samarium cobalt blank with a certain strength.
[0044] Specifically, before the powder pressing step, a smelting and powder making step is also included. The composition of the samarium cobalt A powder and the samarium cobalt B powder is: Sm content is 24-26wt.%, Fe content is 17-20wt.%, Cu content is 4-7wt.%, Zr content is 2-3wt.%, and the rest is Co.
[0045] It should be noted that the raw materials of SmCo A powder and SmCo B powder are weighed according to the weight ratio of each element in the Sm (CoFeCuZr) z alloy, mixed and vacuum induction smelted to make alloy ingots, wherein the composition of the alloy ingots is: Sm content 24-26wt.%, Fe content 17-20wt.%, Cu content 4-7wt.%, Zr content 2-3wt.%, and the rest is Co. After the ingredients are prepared, 3-10wt.% of Sm is added to compensate for the burning loss. Subsequently, the ingots are coarsely crushed and medium crushed, and then air flow milled to obtain SmCo A powder with a particle size of 1-2μm and SmCo B powder with a particle size of 3-4μm.
[0046] Specifically, the purity of Sm is required to be no less than 99.5wt.%, the purity of Co is required to be no less than 99.9wt.%, and the smelting vacuum degree is no higher than 10-2Pa.
[0047] Specifically, after the powder pressing step, a sintering and solid solution step is also included. The sintering conditions are heating to 200°C-500°C, keeping the temperature for 0.5-2h, then heating to 1195-1220°C, and keeping the temperature for 0.5-5h.
[0048] Specifically, the heating temperature of the solid solution is 1160-1190° C., and the holding time is 2-12 hours.
[0049] It should be noted that sintering, solution treatment and aging treatment are required in the present invention. Sintering refers to heating and compacting the powdered samarium-cobalt alloy at a certain temperature and pressure so that the particles are combined with each other to form a block material of a certain shape and size. This process can significantly improve the density and strength of the material.
[0050] The main purpose of solution treatment is to improve the plasticity and toughness of steel or alloy, strengthen the solid solution, improve toughness and corrosion resistance, eliminate stress and soften, so as to continue processing or forming. For samarium cobalt alloy, solution treatment can further improve its structure and performance, and prepare for subsequent aging treatment.
[0051] Specifically, after the sintering and solutionizing step, an aging treatment step is also included to obtain a samarium cobalt magnet; wherein the aging temperature is 800-900°C, the holding time is 4-24h, the temperature is lowered to 350-500°C at a cooling rate of 0.5-2°C / min, and the temperature is kept for 2-15h.
[0052] It should be noted that in samarium cobalt alloy, aging treatment can eliminate the residual stress generated during sintering and solid solution, improve the toughness and heat resistance of the material, and also help to further improve the hardness and strength of the material.
[0053] The present invention also provides a samarium cobalt magnet with high mechanical properties, which is prepared by the following steps, specifically:
[0054] S1: smelting and powder making;
[0055] S2: Spreading powder alternately, spreading Sm-cobalt A powder and Sm-cobalt B powder alternately, ensuring that the bottom layer and the top layer are Sm-cobalt B powder, and the particle sizes of Sm-cobalt A powder and Sm-cobalt B powder are different; the weight of the Sm-cobalt A powder is 5wt.%-50wt.%, and the weight of the Sm-cobalt B powder is 95wt.%-50wt.%.
[0056] S3: sintering and solid solution;
[0057] S4: Samarium cobalt magnets are obtained after aging treatment.
[0058] It should be noted that the samarium cobalt magnet is obtained according to the above preparation steps, especially after the alternating powder spreading step, which replaces the traditional mixed powder spreading method, not only can the bending strength of the samarium cobalt magnet be improved, but also the magnetic properties of the samarium cobalt magnet can be guaranteed. The magnetic energy product of the samarium cobalt magnet is above 28MGOe and the bending strength is above 140MPa.
[0059] In order to more clearly describe the present invention, it is further illustrated by the following examples and comparative examples.
[0060] Examples 1-7, Comparative Example 1
[0061] (1) According to the weight ratio of each element in the Sm(CoFeCuZr)z alloy, the raw materials are weighed, mixed and then vacuum induction smelted to make an alloy ingot, wherein the composition of the alloy ingot is: Sm content 24wt.%, Fe content 17wt.%, Cu content 4.5%, Zr content 2.2wt.%, and the rest is Co. After the ingredients are prepared, an additional 5wt.% of Sm is added to compensate for the burn loss. The purity of the main raw material Sm is required to be no less than 99.5wt.%, and the purity of Co is required to be no less than 99.9wt.%, and the melting vacuum is not higher than 10 -2 Pa.
[0062] (2) The alloy ingot is coarsely crushed and medium crushed, and then air flow milled to obtain powder A and powder B. The particle sizes of powder A and powder B are shown in Table 1.
[0063] (3) After mixing powder A and powder B for 1-3 hours, the powders are distributed, wherein the weight of powder A and powder B are shown in Table 1. Powder A is divided into n parts by weight, and powder B is divided into n+1 parts by weight, as shown in Table 1. The distribution method is to alternate powder B and powder A, that is, powder B-powder A-powder B powder... powder B-powder A-powder B powder, ensuring that the bottom and top layers are powder B. The powder is placed in a magnetic field with a magnetic field strength of 2.0 T for orientation molding, and then cold isostatic pressing is performed at a pressure of 250 MPa for 30 seconds to obtain a samarium cobalt blank.
[0064] (4) The blank obtained in step 3 is placed in an inert gas for sintering and solid solution. The sintering conditions are heating to 500°C, keeping the temperature for 0.5 h, then heating to 1195°C, keeping the temperature for 3 h. The solid solution conditions are 1160°C, keeping the temperature for 10 h.
[0065] (5) The blank obtained in step 4 is placed in an inert gas for aging at 850°C for 18 hours, then cooled to 400°C at a cooling rate of 0.5-2°C / min and kept at this temperature for 6 hours.
[0066] Comparative Example 2
[0067] (1) According to the weight ratio of each element in the Sm(CoFeCuZr)z alloy, the raw materials are weighed, mixed and then vacuum induction smelted to make an alloy ingot, wherein the composition of the alloy ingot is: Sm content 24wt.%, Fe content 17wt.%, Cu content 4.5%, Zr content 2.2wt.%, and the rest is Co. After the ingredients are prepared, an additional 5wt.% of Sm is added to compensate for the burn loss. The purity of the main raw material Sm is required to be no less than 99.5wt.%, and the purity of Co is required to be no less than 99.9wt.%, and the melting vacuum is not higher than 10 -2 Pa.
[0068] (2) The alloy ingot is coarsely crushed, medium crushed, and then air flow milled to obtain powder A and powder B, wherein the average particle size of powder A and the average particle size of powder B are both 2.5 μm.
[0069] (3) After mixing powder A and powder B for 1-3 hours, the powders are spread. After mixing powder A and powder B, the powders are placed in a magnetic field with a magnetic field strength of 2.0 T for orientation molding without layering and then cold isostatically pressed at a pressure of 250 MPa for 30 seconds to obtain a samarium cobalt blank.
[0070] (4) The blank obtained in step 3 is placed in an inert gas for sintering and solid solution. The sintering conditions are heating to 500°C, keeping the temperature for 0.5 h, then heating to 1195°C, keeping the temperature for 3 h. The solid solution conditions are 1160°C, keeping the temperature for 10 h.
[0071] (5) The blank obtained in step 4 is placed in an inert gas for aging at 850°C for 18 hours, then cooled to 400°C at a cooling rate of 0.5-2°C / min and kept at this temperature for 6 hours.
[0072] Comparative Example 3
[0073] (1) According to the weight ratio of each element in the Sm(CoFeCuZr)z alloy, the raw materials are weighed, mixed and then vacuum induction smelted to make an alloy ingot, wherein the composition of the alloy ingot is: Sm content 24wt.%, Fe content 17wt.%, Cu content 4.5%, Zr content 2.2wt.%, and the rest is Co. After the ingredients are prepared, an additional 5wt.% of Sm is added to compensate for the burn loss. The purity of the main raw material Sm is required to be no less than 99.5wt.%, and the purity of Co is required to be no less than 99.9wt.%, and the melting vacuum is not higher than 10 -2 Pa.
[0074] (2) The alloy ingot is coarsely crushed, medium crushed, and then air flow milled to obtain powder A and powder B, wherein the average particle size of powder A is 1.8 μm and the average particle size of powder B is 3.8 μm.
[0075] (3) After mixing powder A and powder B for 1-3 hours, the powders are distributed, wherein the weight of powder A is 35% and the weight of powder B is 65%. After mixing powder A and powder B, the powders are placed in a magnetic field with a magnetic field strength of 2.0T for orientation molding without layering and then cold isostatically pressed at a pressure of 250MPa for 30 seconds to obtain a samarium cobalt blank.
[0076] (4) The blank obtained in step 3 is placed in an inert gas for sintering and solid solution. The sintering conditions are heating to 500°C, keeping the temperature for 0.5 h, then heating to 1195°C, keeping the temperature for 3 h. The solid solution conditions are 1160°C, keeping the temperature for 10 h.
[0077] (5) The blank obtained in step 4 is placed in an inert gas for aging at 850°C for 18 hours, then cooled to 400°C at a cooling rate of 0.5-2°C / min and kept at this temperature for 6 hours.
[0078] Table 1 Parameter comparison of Examples 1-7 and Comparative Examples 1-3
[0079]
[0080] *When n=0, alternating powder spreading is not adopted.
[0081] Performance Testing
[0082] The above-mentioned Examples 1-7 and Comparative Examples 1-3 were tested, mainly including the testing of mechanical properties and magnetic properties. The specific test results are shown in Table 2.
[0083] Table 2 Test results
[0084]
[0085] Combining Examples 1-7 and Comparative Examples 1-3 with Table 2, it can be seen that the samarium cobalt magnet obtained by the preparation method provided by the embodiment of the present invention not only has a high bending strength, but also has excellent magnetic properties. After testing, the bending strength of the obtained samarium cobalt magnet is above 145MPa, the maximum magnetic energy product is above 28.11MGOe; the density is 8.40-8.47g / cm 3 ; Remanence is above 10.77kGs; Intrinsic coercivity is above 26.32kOe.
[0086] The above Examples 1-4 and Comparative Example 2 were observed by scanning electron microscope. Figure 1-5 As shown. Figure 1-4 It can be seen that the samarium cobalt magnets prepared by the preparation methods of Examples 1-4 have small grains aggregated, and the formed fine grain area can effectively prevent the further spread of microcracks, thereby improving the mechanical properties of the magnet. Figure 5 It can be seen that the samarium cobalt magnet obtained by the preparation method of Comparative Example 2 does not have such fine grain areas, so its mechanical properties are poor.
[0087] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for preparing a samarium cobalt magnet with high mechanical properties, characterized in that: The method comprises a powder spreading and pressing step, in which samarium cobalt A powder and samarium cobalt B powder are alternately spread to ensure that the bottom layer and the top layer are samarium cobalt B powder, and the particle sizes of the samarium cobalt A powder and the samarium cobalt B powder are different; the weight of the samarium cobalt A powder is 5wt.%-50wt.%, and the weight of the samarium cobalt B powder is 95wt.%-50wt.%.
2. The method for preparing the samarium cobalt magnet with high mechanical properties according to claim 1, characterized in that: The samarium cobalt A powder is divided into n parts by weight, and the samarium cobalt B powder is divided into n+1 parts by weight, wherein n≥3.
3. The method for preparing the samarium cobalt magnet with high mechanical properties according to claim 1, characterized in that: The weight of the samarium cobalt A powder is 5wt.%-35wt.%, and the weight of the samarium cobalt B powder is 95wt.%-65wt.%.
4. The method for preparing the samarium cobalt magnet with high mechanical properties according to claim 1, characterized in that: The particle size of the samarium cobalt B powder is larger than that of the samarium cobalt A powder. The particle size of the samarium cobalt A powder is 1-2 μm, and the particle size of the samarium cobalt B powder is 3-4 μm.
5. The method for preparing the samarium cobalt magnet with high mechanical properties according to claim 1, characterized in that: The mixed powder is placed in a magnetic field with a magnetic field strength of 1.8T-2.0T for orientation molding, and then cold isostatic pressing is performed at a pressure of 180MPa-300MPa for 10-60 seconds to obtain a samarium cobalt blank.
6. The method for preparing the samarium cobalt magnet with high mechanical properties according to claim 1, characterized in that: Before the powder pressing step, a smelting and powder making step is also included. The compositions of the samarium cobalt A powder and the samarium cobalt B powder are: Sm content 24-26wt.%, Fe content 17-20wt.%, Cu content 4-7wt.%, Zr content 2-3wt.%, and the rest is Co.
7. The method for preparing the samarium cobalt magnet with high mechanical properties according to claim 1, characterized in that: After the powder pressing step, a sintering and solid solution step is also included. The sintering conditions are heating to 200° C.-500° C., keeping the temperature for 0.5-2 hours, then heating to 1195-1220° C., and keeping the temperature for 0.5-5 hours.
8. The method for preparing the samarium cobalt magnet with high mechanical properties according to claim 7, characterized in that: After the sintering and solid solution step, an aging treatment step is also included to obtain a samarium cobalt magnet; wherein the aging temperature is 800-900°C, the holding time is 4-24h, the temperature is reduced to 350-500°C at a cooling rate of 0.5-2°C / min, and the temperature is kept for 2-15h.
9. The method for preparing the samarium cobalt magnet with high mechanical properties according to claim 8, characterized in that: The magnetic energy product of the samarium cobalt magnet is above 28 MGOe, and the bending strength is above 140 MPa.
10. A samarium cobalt magnet with high mechanical properties, characterized in that: The method is prepared according to any one of claims 1 to 9.
Citation Information
Cited By
Samarium cobalt permanent magnet and preparation method and application thereof
CN119905309A
Sintered samarium-cobalt magnet and preparation method thereof
CN120432253A
Samarium cobalt permanent magnet material and preparation method thereof
CN120854157A